2021
DOI: 10.1177/11786337211018722
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to National Consensus Guidelines and Association with Clinical Outcomes in Patients with Candidemia

Abstract: Background: National consensus guidelines outline recommendations for best practices in treating patients with candidemia. This study evaluated the impact of receiving care adherent to the best practice recommendations on clinical outcomes in patients with candidemia. Methods: This retrospective, multicenter study included patients with candidemia from 2010 to 2015 at 9 hospitals. The primary outcome was the composite of 30-day in-hospital mortality and 90-day candidemia recurrence. Outcomes were compared betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Furthermore, this is especially true in the case of additional renal failure with renal replacement therapy. All current guidelines also recommend the removal of central lines in CBSI, which is further supported by recent studies [ 24 , 34 , 43 , 44 , 45 , 46 ]. Since ECMO cannulas cannot usually be exchanged or removed, this recommendation is difficult to fulfill.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, this is especially true in the case of additional renal failure with renal replacement therapy. All current guidelines also recommend the removal of central lines in CBSI, which is further supported by recent studies [ 24 , 34 , 43 , 44 , 45 , 46 ]. Since ECMO cannulas cannot usually be exchanged or removed, this recommendation is difficult to fulfill.…”
Section: Discussionsupporting
confidence: 56%
“…Junco et al 18 assessed guideline adherence to the US National Consensus Guidelines for Candidemia and demonstrated a much lower rate of adherence (31.3% [50/160]) for initial echinocandin dose. We propose the differences in adherence may be due to the guidelines used.…”
Section: Discussionmentioning
confidence: 99%
“…We propose the differences in adherence may be due to the guidelines used. Many international studies assess guideline adherence of candidemia management, 18,19 assessing antifungal use, and a suite of other recommendations, including the removal of central venous catheters (CVCs) and repeat blood cultures. 5 Study heterogeneity makes it challenging to compare literature assessing antifungal choice, guideline compliance, and appropriateness.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the study showed no higher mortality or recurrence based on treatment duration but highlighted that the most common reason for failure to receive appropriate initial antifungal treatment was omission of the loading dose (Table 1). 27 …”
Section: Methodsmentioning
confidence: 99%
“…While investigating late recurrence of candidemia, defined by two episodes of candidemia at least 30 days apart, several available reports suggest that treatment duration might not exert a significant impact on recurrence rates or even survival outcomes 21,27 . This finding highlights the intricate nature of candidemia as a medical entity and emphasises the need for a comprehensive assessment when determining the optimal treatment duration for individual patients.…”
Section: Exploring the Ideal Treatment Durationmentioning
confidence: 99%